“We are Maine”—Is There an Authentic Maine Public Policy? - Anderson, Mark; Noblet, Caroline (Maine Policy Review, 2020)
The authors explore whether there is something about how policy is developed, approved, and implemented—or something about the content of policy—that is based upon Maine as place? Is there a genuine Maine public policy that reflects the unique demography, geography, and culture of this place? Or is the work of policy here essentially the same as anywhere else in our democracy?
Keywords: Baxter State Park; sugar beets; Friends of Bigelow; Maine energy development; tree growth law; farmland and open space programs; bear-hunting referenda